Avaliação dos diferentes métodos de transformação para georreferenciar documentos cartográficos de 1812 e 1906 do Rio de Janeiro - Cláudio Chagas Figueiredo; Renato Fontes Guimarães; Paulo Márcio Leal de Menezes; Osmar Abilio de Carvalho Junior; Luiz Felipe Coutinho Ferreira da Silva (Confins)
The historical cartography has a key role in understanding the various changes that have happened in space over time. Thus, the development of an accurate georeferencing of ancient cartographic documents retrieved, became essential for urban development monitoring, considering the action of various actors involved, as the public policies adopted by governments, real estate speculation, the church's influence , among others, led to the current format of the Rio de Janeiro city. Thus, the study aims to evaluate the results of different types of transformation processing (geometric, affine and polynomial) that provides better accuracy in georeferencing the São Sebastiâo do Rio de Janeiro (1812) map and planta de melhoramentos urbanos da cidade do Rio de Janeiro, published in 1906, based on the digital map of Rio de Janeiro city, 2000. The methodology was divided in the follow stages: a) Cartographic choices from the map projection, b) Georreferencing procedures and c) Processing of 1812 and 1906 maps. The results demonstrate that the residual error is compatible with 1:10,000 scale and both plants may be used for analysis over time.